Liquidity, Solvability, Profitability Analysis of JRPT (2021-2025) - Ayu Nilamsari; Heni Devita; Saibatul Aslamiyah; Sylfiah Mau`izah; Sofi Siti Sofiah; Zahro Zaqiyatul Widia; Herayati Herayati (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study analyzes the financial performance of PT Jaya Real Property Tbk (JRPT) during the 2021–2025 period through liquidity, solvency, and profitability ratios. The research applies a descriptive quantitative method using secondary data obtained from the company’s annual financial statements. Liquidity is evaluated through the Current Ratio (CR) and Quick Ratio (QR), solvency through the Debt to Asset Ratio (DAR) and Debt to Equity Ratio (DER), and profitability through Return on Assets (ROA) and Return on Equity (ROE). The calculated ratios are compared annually to identify changes in short-term payment capacity, capital structure, financial risk, and the efficiency of asset and equity utilization. The results show that JRPT’s liquidity fluctuated, with its weakest position occurring in 2023 when the CR reached 0.87 and the QR reached 0.13. Liquidity subsequently recovered, as the CR increased to 1.25 and the QR to 0.38 in 2025. Solvency improved consistently, indicated by the decline in DAR from 30.60% to 27.56% and DER from 43.53% to 38.04%. Profitability also strengthened, with ROA rising from 7.13% to 8.71% and ROE from 10.27% to 12.03%. These findings indicate that JRPT maintained a relatively healthy capital structure, reduced its dependence on debt, and improved its capacity to generate returns. Nevertheless, the low quick ratio requires continued attention because a substantial portion of current assets remains tied to property inventories. Overall, JRPT demonstrated resilient and improving financial performance despite property-sector uncertainty.